KESESUAIAN RESEP BERDASARKAN ASPEK ADMINISITRATIF DAN FARMASETIK PADA PASIEN RAWAT JALAN DI PUSKESMAS WANARAJA GARUT - Nurul, Nurul; Sujana, Dani; Rahayu, Sri (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2024)
Completeness of administration and pharmacology in prescriptions can minimise or reduce the occurrence of medication errors. This study aims to look at the description of the suitability of administrative and pharmaceutical aspects in prescriptions by looking at the percentage of completeness of administrative and pharmaceutical aspects in prescriptions at the Wanaraja Garut Health Centre. This research is quantitative descriptive. The sampling method is random sampling which is calculated using the Slovin formula. The sample used was 308 prescription sheets in January 2021. Based on the results of the description of the completeness of prescriptions at the Wanaraja Garut Health Centre, of the 308 prescription sheets studied administratively, it was found that 60.90% were complete and 39.10% were incomplete, and studied pharmaceutically, it was found that 93.33% of the prescriptions were appropriate and 6.67% of the prescriptions were not appropriate. It can be concluded that the prescription sheet at the Wanaraja Garut Health Centre almost entirely meets the aspects of the completeness of the prescription in accordance with applicable laws and regulations, but it is still found that 11 out of 16 aspects of the completeness of the prescription do not contain information, namely the patient's age 2.27%, gender 30.51%, patient weight 98.51%, patient address 8.76%, doctor's name 47.7%, doctor's initials 64.28%, prescription date 3.57%, doctor's room or unit of origin 43.83%, doctor's SIP No. 0%, dosage form 11.3%, drug dosage 28.88%. This shows that the completeness of prescriptions at the Wanaraja Garut Health Centre is still incomplete, in writing prescriptions that trigger medication errors. It needs to be improved so that it meets the standards in accordance with applicable laws and regulations.